EARNINGS PER SHARE, RETURN ON EQUITY, INFLATION, AND INTEREST RATES ON STOCK PRICE - Febtia Devi Ananti; Nurlaela, Siti; Masitoh, Endang (Jurnal RAK (Riset Akuntansi Keuangan), 2024)
This study aims to test and analyze the effect of earnings per share (EPS), return on equity (ROE), inflation, and interest rates on stock prices. The research population consists of consumer goods industry companies listed on the Indonesia Stock Exchange (IDX) during the period 2018 to 2022. This study used a purposive sampling technique with specific criteria. The samples of this study consist of 29 companies with a total of 126 observations. The analysis was carried out using a multiple linear regression approach. The results showed that earnings per share (EPS) has a positive effect on stock prices meanwhile return on equity (ROE) has a negative effect on stock prices. On the other side, inflation and interest rates do not affect stock prices.